Polycystic Ovary Syndrome and Reproductive Health: A Comprehensive Review - Ramadan S. Hussein; Salman Bin Dayel; Othman Abahussein (Clinical and Experimental Obstetrics & Gynecology)
Objectives: Polycystic ovary syndrome (PCOS) is a prevalent and intricate endocrine disorder that impacts women of reproductive age. It is marked by various symptoms, including menstrual irregularities, hyperandrogenism, and metabolic dysfunctions, with significant implications for reproductive and overall health. This review aims to provide a comprehensive analysis of the impact of PCOS on reproductive health, highlighting the underlying pathophysiology, clinical manifestations, and emerging therapeutic approaches. Mechanism: The current literature was detailed, focusing on the hormonal imbalances associated with PCOS, including androgen excess, insulin resistance, and dysregulation of the hypothalamic-pituitary-ovarian (HPO) axis. The review also explored genetic and environmental factors contributing to PCOS and described the characteristic ovarian morphology. Findings in Brief: The findings reveal that PCOS is not only a leading cause of infertility but also contributes to a spectrum of metabolic and psychological issues. Recent research highlights the role of inflammation, the gut microbiome, and novel therapies in managing PCOS. Despite advances, gaps in understanding the long-term implications of PCOS on reproductive health remain. Conclusions: The review underscores the need for individualized and holistic treatment strategies in managing PCOS, integrating emerging therapies and mental health support. Continued research is vital to improving patient outcomes and advancing the management of this multifaceted condition.